2022
DOI: 10.3390/app12031326
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Analytical Tools for the Estimation of Gut Permeability of Compounds of Pharmaceutical Interest

Abstract: The present study aims at developing a quantitative structure–activity relationship (QSAR) model for the determination of gut permeability of 228 pharmacological drugs at different pH conditions (3, 5, 7.4, 9, intrinsic). As a consequence, five different datasets (according to the diverse permeability shown by the compounds at the different pH values) were handled, with the aim of discriminating compounds as low-permeable or high-permeable. In order to achieve this goal, molecular descriptors for all the inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It cannot be ignored that for compounds C4 and D5 longer incubation time could alter the presented results, providing measurable permeability. Some authors have reported conducting PAMPA measurements in a period of over 48 h to achieve higher accuracy for low‐permeable compounds (Biancolillo et al, 2022; Oja et al, 2019; Oja & Maran, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be ignored that for compounds C4 and D5 longer incubation time could alter the presented results, providing measurable permeability. Some authors have reported conducting PAMPA measurements in a period of over 48 h to achieve higher accuracy for low‐permeable compounds (Biancolillo et al, 2022; Oja et al, 2019; Oja & Maran, 2018).…”
Section: Discussionmentioning
confidence: 99%